2007
DOI: 10.1099/vir.0.82321-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity obtained from aqueous extracts of the Chilean soapbark tree (Quillaja saponaria Molina)

Abstract: Natural, aqueous extracts of Quillaja saponaria, the Chilean soapbark tree, contain several physiologically active triterpenoid saponins that display strong adjuvant activity when used in either human or animal vaccines. In this paper, we describe studies that demonstrate a novel antiviral activity of Quillaja extracts against six viruses: vaccinia virus, herpes simplex virus type 1, varicella zoster virus, human immunodeficiency viruses 1 and 2 (HIV-1, HIV-2) and reovirus. We demonstrate that microgram amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 45 publications
2
36
1
Order By: Relevance
“…Based on these results, we tested for antiviral activity at Quillaja extract concentrations of 1.0 and 9.5 mg/ml. We have previously demonstrated the activity of Ultra Dry 100 Q against reovirus [46] and we have included reovirus in this study to permit comparisons to be made to the newly reported antiviral activity against a related virus, rotavirus. This study presents new findings and evaluates the antiviral activity of the highly purified saponin extract, VaxSap, against both of these viruses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, we tested for antiviral activity at Quillaja extract concentrations of 1.0 and 9.5 mg/ml. We have previously demonstrated the activity of Ultra Dry 100 Q against reovirus [46] and we have included reovirus in this study to permit comparisons to be made to the newly reported antiviral activity against a related virus, rotavirus. This study presents new findings and evaluates the antiviral activity of the highly purified saponin extract, VaxSap, against both of these viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Saponins offer the possibility of a new virucidal mechanism of action, interaction with viral envelopes leading to their destruction and/or interaction with host cell membranes leading to a loss of viral binding sites [45]. We have previously demonstrated the activity of Ultra Dry 100 Q against reovirus [46] and we have included reovirus in this study to permit comparisons to be made between the earlier study and this current study reporting strong antiviral activity against a related virus, rotavirus. This current study presents new findings of antiviral activity against rotavirus, the leading single cause of severe diarrhea among infants and young children, and one of several viruses that cause infections commonly known as ‘stomach flu’, despite having no relation to influenza.…”
mentioning
confidence: 97%
“…Two live oral vaccines, Rotarix and RotaTeq have shown great efficacy in reducing rotavirus related hospitalization and death among young children in developing countries(Ruiz-Palacios et al, 2006; Vesikari et al, 2004), but not in most developing countries in Asia and Africa(Moon et al, 2010). This current study is a continuous work that builds on the previous work performed with Ultra Dry 100 Q and Vax Sap (Roner et al, 2007; Roner et al, 2010). This study was conducted in Balb/c mice that were inoculated with Rhesus Rotavirus (RRV) and treated with Quillaja saponins to investigate the anti-rotavirus activity of saponins in vivo .…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that the saponins are not directly virucidal but that the antiviral activity involves an inhibition of virus-host cell interaction and subsequent attachment (Amoros et al, 1988; Roner et al, 2007; Roner et al, 2010). Viral inactivation by saponins has also been suggested to involve interactions with membrane glycoproteins following the observation that no direct virucidal effect is seen on the nonenveloped poliovirus (Rao and Sinsheimer, 1974; Ushio and Abe, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This species is well known for its content of triterpene saponins (between 8.5 and 16.4%) that are widely used in industry, in personal care products and as vaccine adjuvants. Related triterpene glycosides and their aglycones have been shown to possess anti-inflammatory, antiallergic, antiviral, antifungal and cytotoxic properties (Roner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%